Expression of ZO‐1 and claudin‐1 in a 3D epidermal equivalent using canine progenitor epidermal keratinocytes. Issue 4 (21st May 2018) - Teramoto, Keiji; Asahina, Ryota; Nishida, Hidetaka; Kamishina, Hiroaki; Maeda, Sadatoshi
Abstract : Background: Previous studies indicate that tight junctions are involved in the pathogenesis of canine atopic dermatitis (cAD). An in vitro skin model is needed to elucidate the specific role of tight junctions in cAD. A 3D epidermal equivalent model using canine progenitor epidermal keratinocytes (CPEK) has been established; the expression of tight junctions within this model is uncharacterized. Hypothesis/Objectives: To investigate the expression of tight junctions in the 3D epidermal equivalent. Animals: Two normal laboratory beagle dogs served as donors of full‐thickness skin biopsy samples for comparison to the in vitro model. Methods: Immunohistochemical techniques were employed to investigate the expression of tight junctions including zonula occludens (ZO)‐1 and claudin‐1 in normal canine skin, and in the CPEK 3D epidermal equivalent. Results: Results demonstrated the expression of ZO‐1 and claudin‐1 in the CPEK 3D epidermal equivalent, with staining patterns that were similar to those in normal canine skin. Conclusions and clinical importance: The CPEK 3D epidermal equivalent has the potential to be a suitable in vitro research tool for clarifying the specific role of tight junctions in cAD. Abstract : Background – Previous studies indicate that tight junctions are involved in the pathogenesis of canine atopic dermatitis (cAD). An in vitro skin model is needed to elucidate the specific role of tight junctions in cAD. A 3D epidermal equivalent model using canine progenitor epidermal keratinocytes (CPEK) has been established; the expression of tight junctions within this model is uncharacterized.Hypothesis/Objectives – To investigate the expression of tight junctions in the 3D epidermal equivalent.Conclusions and clinical importance – The CPEK 3D epidermal equivalent has the potential to be a suitable in vitro research tool for clarifying the specific role of tight junctions in cAD.